ANALISIS KEMAMPUAN MENYELESAIKAN MASALAH MATEMATIKA SOAL HOTS DITINJAU DARI KEPERCAYAAN DIRI PADA SISWA KELAS VIII SMP NEGERI 5 PALLANGGA [AN ANALYSIS OF STUDENTS’ ABILITY TO SOLVE HOTS PROBLEMS BASED ON SELF-CONFIDENCE LEVELS IN A GRADE 8 MATHEMATICS CLASS AT SMP NEGERI 5 PALLANGGA] - Waliq, M Nur Al Awwalul; Sukmawati, Sukmawati; Mahmud, Randy Saputra (JOHME: Journal of Holistic Mathematics Education, 2021)
This study describes students' ability to solve HOTS problems according to their self-confidence level in a grade 8 class at a junior high school in Pallangga. The type of research used is descriptive qualitative research. The research procedure includes the preparation, implementation, and analysis stages of research results. The subjects in the study were 3 grade 8 students at SMP Negeri 5 in the district of Pallangga. The subjects were selected by giving a questionnaire to all grade 8 students to select students who had high self-confidence, moderate self-confidence, and low self-confidence. The research refers to the four stages of the ability to solve mathematical problems based on Polya's steps, namely: understanding the problem, planning problem-solving strategies, carrying out calculations, and evaluating the results of problem-solving. The research instrument was a self-confidence questionnaire, an ability test to solve HOTS math problems based on Polya's steps, and interview guidelines. The results showed that there were differences in the ability to solve mathematical HOTS questions based on Polya's steps by the three selected subjects. The results showed that subjects with high self-confidence and moderate self-confidence were able to meet the indicators of understanding the problem, while subjects with low self-confidence were unable to meet the indicators of understanding the problem. At the stage of planning a problem-solving strategy, subjects with high self-confidence and moderate self-confidence were able to meet the indicators, while subjects with low self-confidence were unable to meet the indicators. At the stage of carrying out calculations, subjects with high self-confidence were able to meet the indicators, while subjects with moderate self-confidence and low self-confidence were unable to meet the indicators. And at the stage of re-examining the results of problem-solving, subjects with high self-confidence were able to meet the indicators, while subjects with moderate self-confidence and low self-confidence were unable to meet the indicator.BAHASA INDONESIA ABSTRACT: Penelitian ini bertujuan untuk mendeskripsikan kemampuan menyelesaikan masalah matematika soal HOTS ditinjau dari kepercayaan diri pada siswa kelas VIII SMP Negeri 5 Pallangga. Jenis penelitian adalah penelitian deskriptif kualitatif. Prosedur penelitian meliputi persiapan, pelaksanaan dan tahap analisis hasil penelitian. Subjek dalam penelitian adalah 3 orang siswa kelas VIII SMP Negeri 5 Pallangga. Subjek dipilih dengan memberikan angket kepada seluruh siswa kelas VIII untuk memilih siswa yang memiliki kepercayaan diri tinggi, kepercayaan diri sedang, dan kepercayaan diri rendah. Penelitian mengacu pada empat tahap kemampuan menyelesaikan masalah matematika berdasarkan langkah Polya yaitu: memahami masalah, merencanakan strategi pemecahan masalah, melaksanakan perhitungan, dan memeriksa kembali hasil penyelesaian masalah. Instrumen penelitian adalah angket kepercayaan diri, tes kemampuan menyelesaikan masalah matematika soal HOTS berdasarkan langkah Polya, dan pedoman wawancara. Hasil penelitian menunjukkan bahwa terdapat perbedaan kemampuan menyelesaikan masalah matematika soal HOTS berdasarkan langkah Polya oleh ketiga subjek yang dipilih. Berdasarkan hasil penelitian diperoleh bahwa subjek dengan kepercayaan diri tinggi dan kepercayaan diri sedang mampu memenuhi indikator memahami masalah, sementara subjek dengan kepercayaan diri rendah tidak mampu memenuhi indikator memahami masalah. Pada tahap  merencanakan strategi pemecahan masalah, subjek dengan kepercayaan diri tinggi dan kepercayaan diri sedang mampu memenuhi indikator, sementara subjek dengan kepercayaan diri rendah tidak mampu memenuhi indikator. Pada tahap melaksanakan perhitugan, subjek dengan kepercayaan diri tinggi mampu memenuhi indikator, sementara subjek dengan kepercayaan diri sedang dan kepercayaan diri rendah tidak mampu memenuhi indikator. Dan pada tahap memeriksa kembali hasil penyelesaian masalah, subjek dengan kepercayaan diri tinggi mampu memenuhi indikator, sementara subjek dengan kepercayaan diri sedang dan kepercayaan diri rendah tidak mampu memenuhi indikator.